Changes in typical beliefs in response to complicated grief treatment. Issue 1 (5th December 2019) - Skritskaya, Natalia A.; Mauro, Christine; Garcia de la Garza, Angel; Meichsner, Franziska; Lebowitz, Barry; Reynolds, Charles F.; Simon, Naomi M.; Zisook, Sidney; Shear, M. Katherine
Abstract: Background: Prolonged grief disorder (PGD) is a new diagnosis in the 11th edition of the International Classification of Diseases, estimated to affect 1 in 10 bereaved people and causing significant distress and impairment. Maladaptive thoughts play an important role in PGD. We have previously validated the typical beliefs questionnaire (TBQ), which contains five kinds of thinking commonly seen in PGD: protesting the death, negative thoughts about the world, needing the person, less grief is wrong, and grieving too much. The current paper examines the role of maladaptive cognition as measured by the TBQ in PGD and its change with treatment. Methods: Among participants in a multisite clinical trial including 394 adults, we examined (a) the relationship between maladaptive thoughts at baseline and treatment outcomes, (b) the relationship between maladaptive thoughts and suicidality at baseline and posttreatment, and (c) the effect of treatment with and without complicated grief therapy (CGT) on maladaptive thinking. Results: TBQ scores were associated with treatment outcomes and were strongly related to suicidal thinking before and after treatment. TBQ scores showed significantly greater reduction in participants who received CGT with citalopram versus citalopram alone (adjusted mean standard error [ SE ] difference, −2.45 [0.85]; p  = .004) and those who received CGT with placebo versus placebo alone (adjusted mean [ SE ] difference, −3.44 [0.90]; p  < .001). Conclusions: Maladaptive thoughts, as measured by the TBQ, have clinical and research significance for PGD and its treatment.